Reconstructing Indigenous Knowledge of Kasepuhan Girijaya for High School Biology Learning: An Ethnoscience Approach - Nadhifa Rohadatul Aisy; Siti Sriyati; Amprasto; Indriyani Rachman (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2026)
Biology learning on ecosystem topics frequently encounters epistemological challenges arising from a disconnect between formal academic science and students' socio-cultural realities, a gap widely recognised in contemporary science education research. The study aimed to reconstruct the Indigenous Knowledge (IK) of Kasepuhan Girijaya into scientifically validated concepts for integration into high school biology curricula. A qualitative approach with an ethnographic design was employed; data were collected through participatory observation, in depth interviews with traditional leaders, and document analysis, and analysed using an interactive model encompassing data condensation, science reconstruction, and pedagogical relevance mapping. The findings suggest that Kasepuhan Girijaya's three tier land zoning system (Leuweung Tutupan, Titipan, and Garapan) demonstrates conceptual alignment with watershed management and soil conservation principles. Twelve IK practices were identified as providing plausible scientific mechanisms, including light intensity regulation, riparian bio engineering, and ecological rest each mappable to Biology Learning Outcomes in the Merdeka Curriculum. These findings are theoretical and analytical in nature; empirical testing of their pedagogical effectiveness remains a direction for future research.